Meet the textperts. - Williams, Jonathan (Mac life)
As any Web maven knows, content is king. But it's not always in the fancy graphics, photos, or video. Most of the work we do on our Macs calls for manipulating text, that is, typing words. We present eight text-savvy Mac apps that make your time at the keyboard more productive--enjoyable even.